Evaluating the evidence for motor-based interventions in developmental coordination disorder: A systematic review and meta-analysis - Smits-Engelsman, Bouwien Catharina; Vinçon, Sabine; Blank, Rainer; Quadrado, Virgínia H.; Polatajko, Helene; Wilson, Peter H. (Research in developmental disabilities, 2018)
Background: As part of the process of creating an update of the clinical practice guidelines for developmental coordination disorder (DCD) (Blank, Smits-Engelsman, Polatajko, & Wilson, 2012), a systematic review of intervention studies, published since the last guidelines statement was conducted. - Aim - The aim of this study was to 1) systematically review the evidence published from January 2012 to February 2017 regarding the effectiveness of motor based interventions in individuals with DCD, 2) quantify treatment effects using a meta-analysis, 3) examine the available information on different aspects of delivery including use of group intervention, duration and frequency of therapy, and 4) identify gaps in the literature and make recommendations for future intervention research. - Method - An electronic search of 5 databases (PubMed, Embase, Pedro, Scopus and Cochrane) was conducted for studies that evaluated motor-based interventions to improve performance for individuals with DCD. - Results - Thirty studies covering 25 datasets were included, 19 of which provided outcomes on standardized measures of motor performance. The overall effect size (Cohen’s d) across intervention studies was large (1.06), but the range was wide: for 11 interventions, the observed effect was large (>0.80), in eight studies moderate (>0.50), and in five it was small or negligible (<0.50). Positive benefits were evident for activity-oriented approaches, body function-oriented combined with activities, active video games, and small group programs. - Conclusion - Results showed that activity-oriented and body function oriented interventions can have a positive effect on motor function and skills. However, given the varied methodological quality and the large confidence intervals of some studies, the results should be interpreted with caution.
Gesehen am 16.12.2019